Characteristics and Acceptability of a Modified High-Energy, High-Protein Enteral Formula Based on Local Foods - Desvianti, Desvianti; Yulianto, Yulianto; Nilawati, Nurul Salasa (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Enteral formula is a liquid nutritional preparation administered orally or via tube to patients with a functioning digestive system, and high-energy high-protein (HEHP) diets are essential for patients requiring enhanced nutritional intake. Objective: To determine the optimal formulation of HEHP enteral formula based on purple sweet potato flour, tempeh flour, and chicken egg flour in terms of macronutrient composition, viscosity, microbiological quality, acceptability, and food cost. Methods: This experimental study used a Completely Randomized Design (CRD) with three formulations tested on 30 panelists for organoleptic evaluation. Results: The organoleptic test results (color, aroma, taste, and texture) indicated that Formula 1 (F1) was the most preferred. F1 contained 124.49 kcal energy, 6.75% protein, 7.25% fat, and 8.06% carbohydrates per 100 grams, with a viscosity of 34.0 mPa.s and a Total Plate Count of 1.0 × 10 colonies/ml, meeting the acceptable microbiological standards for enteral nutrition. Among all formulations, F1 demonstrated optimal sensory quality, nutritional balance, and production cost efficiency, making it the most suitable candidate for HEHP dietary use. Conclusion: The HEHP enteral formula made from purple sweet potato, tempeh, and chicken egg flour is a feasible and acceptable alternative for conscious patients requiring oral HEHP nutritional support.